San Juan de Dios: Centro de Atención y Reintegración para el habitante de calle Ibagué - Tabares Perdomo, Jhonathan Alberto (Universidad Antonio Nariño, 2022)
The problem presented by the city of Ibagué is the lack of care equipment and rehabilitation for the homeless population, which increases consumption and sale of psychoactive substances and the security of the city is affected, because despite being victims of their social condition, some of them also become perpetrators since they are involved in criminal acts to maintain their addiction even violating the rights of other persons.